2009
DOI: 10.1016/j.ijdevneu.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound exposure of the foetal chick brain: effects on learning and memory

Abstract: Ultrasound imaging of the brain is routinely used to monitor the development and resolution of brain lesions among premature and compromised newborn human babies. However, animal studies have shown that ultrasound can cause damage to developing foetal and neonatal tissues. In this study we investigated if ultrasound of the chick brain can lead to learning and memory impairment after hatch. We exposed the brains of chicks on day 19 of a 21 day incubation period to 5 or 10 min of B-mode, or to 1, 2, 3, 4 or 5 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 46 publications
0
27
0
1
Order By: Relevance
“…One specific single specific effect has been described in various publications: a mild increase in the prevalence of non-right handedness among male children exposed to prenatal ultrasound with no other neurological, intellectual, behavioral, or physical anomalies [114][115][116]. Ultrasound has been implicated, in chicks who were insonated in ovo, in learning and memory disturbances [117]. A study failed to demonstrate a relation between ultrasound insonation in utero and decreased intellectual performance [118].…”
Section: Fetal Susceptibility To External Insultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One specific single specific effect has been described in various publications: a mild increase in the prevalence of non-right handedness among male children exposed to prenatal ultrasound with no other neurological, intellectual, behavioral, or physical anomalies [114][115][116]. Ultrasound has been implicated, in chicks who were insonated in ovo, in learning and memory disturbances [117]. A study failed to demonstrate a relation between ultrasound insonation in utero and decreased intellectual performance [118].…”
Section: Fetal Susceptibility To External Insultsmentioning
confidence: 99%
“…Dwell time (duration of exposure) is also of major importance: Ziskin [123] reported that among 15,973 Doppler ultrasound examinations, the average duration was 27 min (and the longest 4 h!). A study in chicken seemed to clearly implicate Doppler [117]. Chicken eggs were insonated on day 19-of a 21-day incubation period.…”
Section: Is Doppler Different and Can It Have Detrimental Effects On mentioning
confidence: 99%
“…This should not completely deter from the study which encourages caution. Another study which demonstrates potential harmful effects of ultrasound (when spectral Doppler is used) showed that even relatively short insonation of chick embryos to clinically relevant Doppler resulted in short-term and medium-term memory loss and a reduced ability to learn [ 82 ].…”
Section: Embryo/fetus Susceptibilitymentioning
confidence: 99%
“…Schneider-Kolsky et al [52] performed a study on the effects on learning and memory of ultrasound exposure of foetal chick brain. Their findings suggested that B-mode exposure on day 19 of a 21 day incubation period had no effect on learning or memory, whereas 4 -5 min of pulsed Doppler ultrasound did.…”
Section: Animal Studiesmentioning
confidence: 99%